A Design and Experimental Investigation of a High-Performance X-Band Patch Array Antenna for Automotive Radar Applications - Lasisi, Hammed Oyebamiji; Ogungbayi, Peter Ropo; Oluwaleke, Afolabi Abimbola (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2025)
Radar technology has become increasingly important in automotive applications, particularly for car-speed detection and monitoring systems. The antenna plays a crucial role in determining the performance of these systems. This paper presents the design, simulation, and experimental investigation of a high-performance X-band patch array antenna for automotive radar applications. The antenna was fabricated and tested, and the experimental results validate the simulation results. The prototype antenna operates at a center frequency of 10 GHz and achieves a gain of 15.48 dB, directivity of 17.96 dBi, and |S11|of -18.85 dB. Its impedance bandwidth extends from 9.69 to 10.20 GHz, with a beam width of 10 degree and corresponding radiation efficiency is 86.17% at 10 GHz. The simulation and experimental results demonstrate excellent agreement, validating the antenna's performance for car-speed detection and monitoring radar systems. The results show that the designed patch array antenna is suitable for automotive radar applications, offering impressive accuracy and reliability.